Metode Peningkatan Tegangan Tarik dan Kekerasan pada Baja Karbon Rendah Melalui Baja Fasa Ganda - Joko Tri Wardoyo (Teknoin, 2005)
This research is conducted to get a method to make-up tension and hardness of low carbon steel through double-phase steel with a specific parameter of heating temperature at 732oC, 770oC, and 810oC with the variation of detention time 5, 10, 20, and 30 minutes. Before conducting the process, all of specimens are normalized at temperature 900oC within 20 minute  to get early condition of homogeneous structure after double phase forming, hereinafter every specimen get the treatment process  at  200oC holding time 20 minutes to make-up of the resilient and less the tension, hereinafter conducted the ossification stretch to make-up the tension and its hardness. Result of this research indicate, that  with the double phase forming at low carbon steel can increase the tension equal to 83% (from 310 N/mm2 to 567 N/mm2) and make-up of hardness 40% (from 133.1 HV to 186.6 HV) which reached with the treatment process at warm-up temperature 770oC with the time during 20 minutes. This result indicates that this method may be used as an alternative to increase of the mechanical nature of low carbon steel. Keywords: low carbon steel, double phase steel